ANALISIS KUALITAS PELAYANAN ONLINE SINGLE SUBMISSION (OSS) PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU (DPMPTSP) PROVINSI BENGKULU - Subhan Ilham Thareq; Ade Fitrah (Gapenas Publisher, 2022)
This study aims to analys the public one single submission (OSS) service carried out by the Bengkulu Province in an effort to improve the quality of public service in Bengkulu Province. OSS is a licensing service system that aims to simplify licensing mechanisms that are integrated with various types of services quickly. Researchers used the qualitative snowball method in exploring and analyzing One Single Submission (OSS) service in Bengkulu Province. The results of the study stated that the OSS services carried out by the Bengkulu Pronvincial Government still require evaluation in the application of the OSS system. Humar resources factors, supporting facilities and infrastructure, internet network, bureaucracy and information aspects are various factors that become obstacles in One Single Submission (OSS) services in Bengkulu Province